Sex trafficking and modern slavery: the absence of evidence - Segrave, Marie Therese (Routledge, 2018)
Introduction -- Search and "rescue" -- In pursuit of justice: identifying victims within the criminal justice system -- In the care of the state -- Prosecution -- Beyond the criminal justice process: the return "home" -- Conclusion